IPO Underpricing: Evidence From Malaysia - Kannan, Shanmugam (2011)
The underpricing of initial public offerings (IPOs) are anomalies well documented by numerous empirical studies. The aim of this thesis is to examine whether or not a variety of different proxies employed under the asymmetric information theory particularly the Winner’s Curse and Signaling models influence underpricing in the Malaysian market. The study used a sample of 125 the Malaysian IPOs in the period between 2005 to 2009. The result shows that gross proceeds, underwriter, insider retention and market capitalization are significant in explaining the degree of underpricing in IPOs. However on other hand, the findings show that age of company and the gap between prospectus and listing dates could not explain the extent of underpricing in Malaysia for the studied period.